Narasi Trauma, Anti-Yahudi, dan Konstruksi Identitas Kolektif Komunitas Yohanian: Membaca Ulang Yohanes 9 Menggunakan Lensa Trauma Kolektif - Kantohe, Finki Rianto (STFT Jakarta, Indonesia, 2024)
Various studies have been conducted to understand the anti-Jewish narratives in the Gospel of John, yet the aspect of trauma is often overlooked. In this paper, I argue that collective trauma plays a significant role in the emergence of anti-Jewish narratives, particularly in John 9, which serves as a trauma narrative to interpret and construct the collective identity of the Johannine community following their expulsion from the synagogue. The article begins with a survey of the development of studies on the Jewish conflict with the Johannine community, along with my critique, followed by an explanation of Jeffrey Alexander's collective trauma theory and James Louis Martyn's two-level drama theory. The conclusion is that hatred toward Jews is not a theological truth or a historical statement from Jesus but part of the process of narrating trauma and constructing collective identity. This aims to prevent readers of John from becoming vicarious trauma carriers that perpetuate anti-Judaism